Courses
Courses for Kids
Free study material
Offline Centres
More
Store Icon
Store

If $\alpha ,\beta $are the complex cube roots of unity, then ${\alpha ^4} + {\beta ^4} + {\alpha ^{ - 1}}{\beta ^{ - 1}} = $
$
  a.{\text{ 1}} \\
  {\text{b}}{\text{. }}\omega \\
  {\text{c}}{\text{. }}{\omega ^2} \\
  {\text{d}}{\text{. 0}} \\
$

seo-qna
Last updated date: 25th May 2024
Total views: 436.8k
Views today: 6.36k
Answer
VerifiedVerified
436.8k+ views
Hint: - Use $\alpha = \omega ,{\text{ }}\beta = {\omega ^2}$

As we know if $\alpha $and $\beta $are the complex cube roots of unity therefore
$1 + \alpha + \beta = 0................\left( 1 \right)$
As we know cube roots of unity are $1,\omega ,{\omega ^2}$
Where $\omega $and${\omega ^2}$are non-real complex cube roots of unity therefore
${\omega ^3} = 1........\left( 2 \right),{\text{ }}1 + \omega + {\omega ^2} = 0...............\left( 3 \right)$
So, from equations (1) and (3)
$\alpha = \omega ,{\text{ }}\beta = {\omega ^2}$
Now given equation is ${\alpha ^4} + {\beta ^4} + {\alpha ^{ - 1}}{\beta ^{ - 1}}$
\[
   \Rightarrow {\omega ^4} + {\left( {{\omega ^2}} \right)^4} + {\omega ^{ - 1}}{\left( {{\omega ^2}} \right)^{ - 1}} \\
   \Rightarrow {\omega ^3}.\omega + {\omega ^8} + {\omega ^{ - 1}}\left( {{\omega ^{ - 2}}} \right) \\
   \Rightarrow {\omega ^3}.\omega + {\left( {{\omega ^3}} \right)^2}{\omega ^2} + \dfrac{1}{{{\omega ^3}}} \\
\]
From equation (2)
$
  {\omega ^3} = 1 \\
   \Rightarrow 1.\omega + {\left( 1 \right)^2}{\omega ^2} + 1 \\
   \Rightarrow 1 + \omega + {\omega ^2} \\
$
From equation (3)
$
  1 + \omega + {\omega ^2} = 0 \\
   \Rightarrow {\alpha ^4} + {\beta ^4} + {\alpha ^{ - 1}}{\beta ^{ - 1}} = 1 + \omega + {\omega ^2} = 0 \\
$
Hence, option (d) is correct.
Note: - Whenever we face such types of problems the key concept is that always remember the condition of cube roots of unity which is stated above, then substitute the values in the given equation then simplify we will get the required answer.